AN OVERVIEW OF THE ALBANIAN PRIVATIZATION PROCESS - Ingrid Konomi (European Scientific Journal, ESJ, 2015)
In the process of transformation of the economy the emphasis is on structural reforms, where one of the supporting pillars of these reforms is the privatization process. Given that, the privatization process in Albania for more than two decades has been the "Achilles heel" of government programs and its impact has been extraordinary in our economy. This paper will provide an overview of the development of this process in Albania, based on the hypothesis that "privatization positively affects the country's economy". What went well and what did not function properly, who can intervene this process in order to improve? Besides tremendous impact on the economy, privatization requires extensive changes in the legislation and urges the creation of institutions that will make this process possible. Privatization is a process based on the political changing role of the government in the economy, but this process in Albania is associated with social consequences such as high unemployment and moderate wages, holidays and layoffs for employees more older and unskilled, retraining, etc.